2021
DOI: 10.3390/cli9060096
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Climate Variability and Trends in Southern Ethiopia

Abstract: This study investigated the trends and variability of seasonal and annual rainfall and temperature data over southern Ethiopia using time series analysis for the period 1983–2016. Standard Anomaly Index (SAI), Coefficient of Variation (CV), Precipitations Concentration Index (PCI), and Standard Precipitation Index (SPI) were used to examine rainfall variability and develop drought indices over southern Ethiopia. Temporal changes of rainfall trends over the study period were detected using Mann Kendall (MK) tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 58 publications
15
37
1
Order By: Relevance
“…The slope of the whole months shows that there is a positive value implying an increase in the mean monthly and seasonal temperature. Belay et al (2021) has revealed similar result in southern Ethiopia. The average monthly and seasonal discharge of the Ajora-Woybo watershed from 1990 to 2015 is depicted in Fig.…”
Section: Analysis Of the Annual Rainfallsupporting
confidence: 60%
See 1 more Smart Citation
“…The slope of the whole months shows that there is a positive value implying an increase in the mean monthly and seasonal temperature. Belay et al (2021) has revealed similar result in southern Ethiopia. The average monthly and seasonal discharge of the Ajora-Woybo watershed from 1990 to 2015 is depicted in Fig.…”
Section: Analysis Of the Annual Rainfallsupporting
confidence: 60%
“…The global hydrological cycle is currently responding to the effects of global warming (IPCC, 2014), which include increased atmospheric water vapor concentration and shifting precipitation patterns (Belay et al, 2021;IPCC, 2014). Hydro-meteorological characteristics have considerably improved the most common forms of natural disasters in Sub-Saharan Africa, particularly in drought and humidity (Serdeczny et al, 2017;Teshome & Zhang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, the impact of climate change on the socio-economic fabric of society is tremendous (Auci et al, 2018). The southern parts of Ethiopia are most vulnerable, with significant rainfall variability and change resulting in prolonged drought and flood occurrences (Belay et al, 2021).…”
Section: Introduction and Problem Statementmentioning
confidence: 99%
“…According to Funk et al [13], continued warming in the Indian Ocean contributes to spring and summer droughts. Climate change is widely believed to be occurring in various parts of Ethiopia [14][15][16]. Observed changes in extremes in the country are dependent on the reliability and quantity of available data.…”
Section: Introductionmentioning
confidence: 99%